The history of Bronze and Iron Age Israel - Matthews, Victor H. (Essentials of biblical studies, 2018)
This volume provides a basic introduction to the historical, archaeological, and contextual aspects of ancient Israel during its formative period in the Bronze and Iron Age. It integrates extrabiblical sources from regions throughout the ancient Near East with the data found in the biblical narratives in order to explore the development of ancient Israelite identity, cultural traditions, and their interaction with the other major cultures of the ancient Near East